Individuals with incident accelerated knee osteoarthritis have greater pain than those with common knee osteoarthritis progression: data from the Osteoarthritis Initiative. Issue 6 (June 2016) - Driban, Jeffrey; Price, Lori; Eaton, Charles; Lu, Bing; Lo, Grace; Lapane, Kate; McAlindon, Timothy
Abstract We evaluated whether accelerated knee osteoarthritis (AKOA) was associated with greater pain and other outcomes and if outcomes varied over time differently among those with incident AKOA or common knee osteoarthritis (KOA), which we defined as a gradual onset of disease. We conducted longitudinal analyses among participants in the Osteoarthritis Initiative who had no radiographic KOA at baseline (Kellgren-Lawrence [KL] <2). Participants were considered AKOA if ≥1 knees progressed to KL grade ≥3 and common KOA if ≥1 knees increased in radiographic scoring within 48 months. We defined the index visit as the study visit when they met the AKOA or common KOA criteria. Our observation period included up to 3 years before and after the index visit. Our primary outcome was WOMAC pain converted to an ordinal scale: none (pain score = 0/1 out of 20), mild (pain score = 2/3), and moderate–severe pain (pain score >3). We explored 11 other secondary outcome measures. We performed an ordinal logistic regression or linear models with generalized estimating equations. The predictors were group (AKOA or common KOA), time (seven visits), and a group-by-time interaction. Overall, individuals with AKOA (n  = 54) had greater pain, functional disability, and global rating scale as well as slower chair-stand and walking pace compared with those with common KOA (n  = 187). There was no significant interaction between group and time for knee pain; however, there was for chair-stand pace and global rating scale. In conclusion, AKOA may be a painful and disabling phenotype that warrants more attention by clinicians and researchers.